2017
DOI: 10.1007/978-3-319-59147-6_40
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of a Brain-Computer Interface and an Eye Tracker: Is There a More Appropriate Technology for Controlling a Virtual Keyboard in an ALS Patient?

Abstract: Abstract. The ability of people affected by amyotrophic lateral sclerosis (ALS), muscular dystrophy or spinal cord injuries to physically interact with the environment, is usually reduced. In some cases, these patients suffer from a syndrome known as locked-in syndrome (LIS), defined by the patient's inability to make any movement but blinks and eye movements. Tech communication systems available for people in LIS are very limited, being those based on eye-tracking and brain-computer interface (BCI) the most u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…They can benefit from BCI solutions that could perform comparably well, or even better than other forms of assistive technology such as eye tracking [3]- [5]. For visual BCI candidates it has been reported [3], [4], [13] that user-comfort is a concern, for which the mVEP paradigm may provide a workable solution.…”
Section: E Visual Bci and Eye-trackingmentioning
confidence: 99%
“…They can benefit from BCI solutions that could perform comparably well, or even better than other forms of assistive technology such as eye tracking [3]- [5]. For visual BCI candidates it has been reported [3], [4], [13] that user-comfort is a concern, for which the mVEP paradigm may provide a workable solution.…”
Section: E Visual Bci and Eye-trackingmentioning
confidence: 99%
“…EEG contributes in both medical diagnosis and biomedical engineering research field in many ways [10] and therefore, greatly supports BCI advancements. People with ALS can communicate through limited number of technological arrangements, among them eye activity-based (for example, eye gaze), and cognitive activity-based (for example, P300 BCI) systems are commonly used [11]. From a comparison study between those two systems for ALS patient, [11] found that BCI is most controllable and comfortable system.…”
Section: Introductionmentioning
confidence: 99%
“…People with ALS can communicate through limited number of technological arrangements, among them eye activity-based (for example, eye gaze), and cognitive activity-based (for example, P300 BCI) systems are commonly used [11]. From a comparison study between those two systems for ALS patient, [11] found that BCI is most controllable and comfortable system. Some patients feel eye-tracking is a stressful system due to frequent eye movements, prolonged eye focus to a particular direction and wearing head mounted eye tracking interface.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth noting that, in the end, the opinion of users is the key to accepting a specific technology. This is because other non-technical aspects, such as fatigue, price, frustration, training time, environment, and so on, are also taken into account [ 35 ]. For example, the authors of [ 36 ] demonstrated that a person with locked-in syndrome (LIS) was able to gain control over an EOG, an eye tracker, and an auditory BCI, but the user preferred to keep employing their low-tech communication method, using residual eye movements, due to their proficiency and that of their caregiver.…”
Section: Introductionmentioning
confidence: 99%